Defective production of interleukin-1 beta in patients with type 2 diabetes mellitus: Restoration by proper glycemic control. (February 2017) - Kousathana, Foteini; Georgitsi, Marianna; Lambadiari, Vaia; Giamarellos-Bourboulis, Evangelos J.; Dimitriadis, George; Mouktaroudi, Maria
Highlights: Type 2 diabetes is associated with risk for inadequate IL-1β monocyte responses. Down-regulation of monocyte NLRP3 inflammasome activation is described. Increased monocyte IL-6 release is also shown. Modulated monocyte function is restored by proper glycemic control. Abstract: The underlying immune defect of susceptibility in diabetes mellitus type 2 to infections remains unknown. The qualitative changes in cytokine biosynthesis by circulating mononuclear cells (PBMCs) and its modulation by glycemic control were investigated. PBMCs were isolated from 39 patients and 25 controls. They were stimulated with purified ligands and heat-killed bacteria in the absence/presence of glucose and NLPR3 inflammasome ligands. Experiments were repeated after 3 and 6 months. Cytokine production was measured in cell supernatants; pro-interleukin(IL)-1 β was measured in cell lysates. Gene expression of IL-1β and activity of caspase-1 were measured as well. Adequate release of interleukin (IL)-1β was found in 42.9% of patients compared to 90% of controls (p: 0.0001). This was related with down-regulation of the NLRP3 inflammasome since gene expression of IL-1β remained unaltered whereas both the ratio of IL-1β to the intracellular pro-IL-1β and the activity of caspase-1 was lower in patients than controls. Addition of glucose did not modify defective IL-1β production. IL-6 production was increased after stimulation with Pam3Cys, phytohemagglutinin and C. albicans . After proper glycemic control, release of IL-1β was increased and of IL-6 decreased; cells of patients with improved glycemic control responded better to LPS stimulation under increased concentrations of glucose. It is concluded that diabetes type 2 is characterized by defective production of IL-1β from circulating monocytes due to impaired activation of the NLRP3 inflammasome and increased production of the anti -inflammatory IL-6. Defects are restored with proper glycemic control.